THE COMPARISON OF PLASMA MALONDIALDEHYDE LEVELS AMONG OSTEOPOROTIC AND NON-OSTEOPOROTIC POSTMENOPAUSAL WOMEN - Innawati Jusup; Putri Theresia LA Bancin; Santoso Jaeri; Banundari Rachmawati (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Introduction: Osteoporosis is a bone metabolic disorder due to decreased of bone matrix and minerals. Oxidative stress refered as an elevation of reactive oxygen species (ROS) in the cells causing structural damages and functional loss, is contributed in the process of osteoporosis, but its association still in controversy. Herewith we report the comparison of the plasma malondialdehyde (MDA) levels, one of oxidative stress markers among osteoporotic postmenopausal women and without osteoporosis. Methods: An observational analytic study with cross-sectional approach among 40 postmenopausal women, grouped into two groups, osteoporosis (n=20) and non-osteoporosis (n=20) based on bone mineral density (BMD) score. The plasma MDA levels were measured from venous blood using ELISA. The difference between plasma MDA levels among both groups was analyzed using an independent T-test. Results: The characteristics of demography and clinic among both groups are relatively similar. However, there is a difference in the body weight and BMI. Furthermore, there is no significant differences of MDA levels between the two groups (292,03±61,02ng/ml for group with osteoporosis, and 315,25±73,86ng/ml for non-osteoporosis, p=0,286). Conclusions: There is no significant difference in plasma MDA levels among osteoporosis and non-osteoporosis postmenopausal women.